Evidence-Based Use of Cognitive Testing for Academic Interventions: A Critical Appraisal of Meta-Analytic Methodologies - Decker, Scott L.; Luedke, Jessica C. (Frontiers in Education, 2021)
Research suggests Specific Learning Disabilities (SLD) are directly linked to specific neurocognitive deficits that result in unexpected learning delays in academic domains for children in schools. However, meta-analytic studies have failed to find supporting evidence for using neurocognitive tests and, consequently, have discouraged their inclusion in SLD identification policies. The current study critically reviews meta-analytic findings and the methodological validity of over 200 research studies used in previous meta-analytic studies to estimate the causal effect of neurocognitive tests on intervention outcomes. Results suggest that only a very small percentage (6 – 12%) of studies used in previous meta-analytic studies were methodologically valid to estimate a direct effect of cognitive tests on academic intervention outcomes, with the majority of studies having no causal link between neurocognitive tests and intervention outcomes. Additionally, significant reporting discrepancies and inaccurate effect size estimates were found that warranted legitimate concerns for conclusions and policy recommendations provided in several meta-analytic studies. Given the lack of methodological rigor linking cognitive testing to academic interventions in current research, removing neurocognitive testing from learning disability evaluations may be premature. Suggestions for future studies evaluating the impact of neurocognitive tests on intervention outcomes as well as guidelines for synthesizing meta-analytic findings are discussed.